Two new species of Paguristes sensu stricto (Decapoda: Anomura: Paguroidea: Diogenidae) and a review of Paguristes pusillus Henderson - Mclaughlin, Patsy A.; Rahayu, Dwi Listyo (Zootaxa, 2005)
A new species of the hermit crab genus Paguristes, sensu stricto, Paguristes alcock n. sp., is described and illustrated from materials collected in Australia, Indonesia and the Philippine Islands. It is proposed that this taxon, or a species identified simply as Paguristes sp. by Lewinsohn (1969) in his monograph of Red Sea Anomura, may be conspecific with the species incorrectly referred by Alcock (1905) and several subsequent carcinologists to Paguristes ciliatus Heller, 1862. Lewinsohn subsequently re-identified his material of Paguristes sp. as Paguristes ciliatus sensu Alcock, 1905 and P. pusillus Henderson, 1896. Alcock’s single specimen of P. ? ciliatus from the Persian Gulf was not available for reexamination. Lewinsohn’s specimens however, have been reviewed and compared with the present authors Indo-Pacific species and with a specimen identified by Henderson as P. pusillus. Lewinsohn’s Red Sea specimens are described and illustrated herein as P. lewinsohni n. sp., as are the specimens identified as P. pusillus by Thompson (1943) from the John Murray Expedition. An illustrated description of P. pusillus is also provided to facilitate recognition of these superficially similar species. Paguristes pusillus zhejiangensis Wang & Tung, 1982 is considered to be a distinct taxon, not a subspecies of P. pusillus, and is herein elevated to full specific rank.